1999
DOI: 10.2118/56856-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foam Quality and Flow Rate on CO2-Foam Behavior at Reservoir Temperature and Pressure

Abstract: This paper reports a series of steady-state CO 2 -foam flow experiments performed at reservoir conditions of 101°F and 2100 psig. Three flow rates ͑total injection rates͒, 4.2, 8.4, and 16.8 cm 3 /h, and five foam qualities, 20%, 33.3%, 50%, 66.7%, and 80%, were used to study how flow rate and foam quality affect foam mobility.Results from these experiments show that foam mobility ͑total mobility of CO 2 /surfactant solution͒ increases with increasing flow rate and foam resistance factor decreases with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…These studies show that a certain range of foam quality exists within which foam is able to reduce mobility and this range depends on chemical and fluid properties, rock properties, as well as injection methodology and rates. Several authors have reported the mobility reducing range to be between 40 to 95% foam qualities [9,21].…”
Section: Foam Qualitymentioning
confidence: 99%
“…These studies show that a certain range of foam quality exists within which foam is able to reduce mobility and this range depends on chemical and fluid properties, rock properties, as well as injection methodology and rates. Several authors have reported the mobility reducing range to be between 40 to 95% foam qualities [9,21].…”
Section: Foam Qualitymentioning
confidence: 99%
“…As a result, sweep efficiency decreases and significant amounts of oil are left behind (Chang and Grigg, 1999;Apaydin and Kovscek, 2001;Panahi, 2004;Le et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During the WAG process, water can reduce the mobility of CO 2 ; it can also trap oil, increase water flow, and decrease the extraction of hydrocarbons from oil by CO 2 (Bernard et al 1980). Besides the water-alternating-gas (WAG) process, the dispersion of CO 2 in water with a suitable foaming agent (surfactant) has been considered as an alternative to reduce CO 2 mobility (Chang and Grigg, 1999;Khalil and Asghari, 2006;Yin et al 2009). In this method, a foaming agent (surfactant) is injected along with CO 2 in the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a foaming agent (surfactant) is injected along with CO 2 in the reservoir. Foam formed by either co-injecting CO 2 and/or alternating with a suitable aqueous foaming agent (Lee et al 1991;Chang and Grigg, 1999) consists of CO 2 macroscopically dispersed in the brine phase. This has an apparent viscosity several orders of magnitude greater than the viscosity of either phase in the dispersion, even at very low foaming agent concentrations (Tabatabal et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation